UTHM Student Attendance System Using Blockchain Technology - Ahmad Danish Adly bin Md Puad,; Nur Ziadah Harun, (Applied Information Technology And Computer Science, 2025)
The UTHM Student Attendance System using Blockchain Technology is designed to enhance the efficiency, data integrity, and traceability of student attendance records. Traditional attendance systems often face issues such as data manipulation and inaccuracies. By integrating blockchain technology, the system ensures immutable and transparent attendance records. The project employs the Prototyping Model, which facilitates iterative development through planning, analysis, design, implementation, and testing phases. The system's core is built using PHP, JavaScript, and Ethereum smart contracts to securely log attendance data. The system is implemented at Universiti Tun Hussein Onn Malaysia (UTHM) to replace conventional methods. The outcome of this system is a robust platform that mitigates fraudulent records, improves data accuracy, and streamlines administrative tasks, benefiting both students and lecturers.